2018
DOI: 10.1159/000491958
|View full text |Cite|
|
Sign up to set email alerts
|

The LncRNA NEAT1 Accelerates Lung Adenocarcinoma Deterioration and Binds to Mir-193a-3p as a Competitive Endogenous RNA

Abstract: Background/Aims: Long noncoding RNAs (lncRNAs) contribute to the development of multiple malignant tumors. Here, we focused on the biological function and underlying molecular mechanism of an lncRNA, nuclear-enriched abundant transcript 1 (NEAT1), in lung adenocarcinoma (LUAD). Methods: In vitro experiments were conducted to determine the biological effects of NEAT1 in LUAD cells. A luciferase activity reporter assay was performed to corroborate the interaction between NEAT1 and miR-193a-3p. Data from Gene Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 42 publications
0
52
0
Order By: Relevance
“…LncRNAs have been well known to exert roles by acting as a competitive endogenous RNA (ceRNA) to segregate microRNAs (miRNAs) away from target mRNAs [15][16][17]. Using bioformatics analysis, we noted that KLF3-AS1 harbors putative binding sites of miR-206.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNAs have been well known to exert roles by acting as a competitive endogenous RNA (ceRNA) to segregate microRNAs (miRNAs) away from target mRNAs [15][16][17]. Using bioformatics analysis, we noted that KLF3-AS1 harbors putative binding sites of miR-206.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, GIT1 was identified as a putative target of miR-206 by harboring a miR-206 binding sequence in the 3ʹ-UTR of its mRNA (Targetscan). LncRNAs have been well known to exert roles by acting as a competitive endogenous RNA (ceRNA) to segregate microRNAs (miRNAs) away from target mRNAs [15][16][17]. Therefore, we speculated that, exosomal KLF3-AS1 derived from MSCs might act as a ceRNA by sponging miR-206 to facilitate GIT1 expression, and thereby promote chondrocyte proliferation and inhibit chondrocyte apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…The process of qRT-PCR has been described in detail in previous studies. [17][18][19] GAPDH served as the reference gene for MIR22HG. Information about the primers for MIR22HG and GAPDH is listed in Table 1.…”
Section: Clinico-pathological Significance Of Mir22hg In Hccmentioning
confidence: 99%
“…For instance, Feng K et al identified that the viability and invasion of papillary thyroid carcinoma cells can be enhanced by lncRNA PVT1 , a ceRNA of miR‐30a, mediating IGF1 receptor expression (Feng et al, ). Yang et al reported that lncRNA HOTTIP accelerates the migration and proliferation of prostate cancer cells by sponging miR‐216a‐5p (Xiong et al, ). After the intersection of bioinformatics prediction results, it was discovered that miR‐128‐3p was highly consistent with HOTTIP ’s 3’UTR sequence.…”
Section: Discussionmentioning
confidence: 99%